2021
DOI: 10.3892/mmr.2021.12094
|View full text |Cite
|
Sign up to set email alerts
|

Major signaling pathways and key mediators of macrophages in acute kidney injury (Review)

Abstract: Acute kidney injury (AKI) has become a global public health problem with high morbidity and mortality rates, as well as high healthcare costs. Immune cells, particularly macrophages, which regulate tissue development, destroy pathogens, control homeostasis and repair wounds, play crucial and complex roles in AKI. In various types of AKI, numerous rapidly recruited monocytes and tissue-resident macrophages act in a coordinated manner. Thus, elucidating the phenotypic and functional characteristics of macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 138 publications
0
11
0
Order By: Relevance
“…This immune cell population was considered as a promising therapeutic target and can potentially be manipulated in a tissue-specific manner. For example, pro-inflammatory macrophage depletion have a universal protective effect on acute kidney injury ( 27 ). Monoclonal antibodies to inhibit macrophagic pro-inflammatory pathways achieve therapeutic efficacy in osteoarthritis ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…This immune cell population was considered as a promising therapeutic target and can potentially be manipulated in a tissue-specific manner. For example, pro-inflammatory macrophage depletion have a universal protective effect on acute kidney injury ( 27 ). Monoclonal antibodies to inhibit macrophagic pro-inflammatory pathways achieve therapeutic efficacy in osteoarthritis ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various signaling pathways play a variety of roles in the functioning of macrophages in periodontal tissues. Different ligands, receptors, enzymes, transcription factors and other molecules closely cooperate to enable macrophages to exert more precise regulatory ability ( 133 ), and different concentrations of the same cytokines can trigger and activate different signaling pathways ( 134 ). Key receptors for the polarization of M1-type macrophages include NOD1 and TLR4, which can individually or synergistically activate NF-ÎşB, MAPK and other signaling pathways, triggering the activation and expression of M1 ( 135 ).…”
Section: Regulatory Mechanisms Based On Polarized Macrophages In Periodontal Tissuementioning
confidence: 99%
“…Unlike the typical acute wound healing process, the conversion of M1 and M2 macrophages is dysregulated in chronic wounds, with 80% of the wound edges being M1 macrophages, which is the biggest contributor to persistent inflammation and eventual scarring of chronic wounds ( Oishi & Manabe, 2018 ). A study using single-cell sequencing of salamander limb regeneration revealed the presence of M2 macrophages early in the regeneration process, suggesting that the specific immune microenvironment constituted by the presence of M2 subtypes early in the limb regeneration process is likely to be the key to scar-free regeneration in salamanders ( Li et al, 2021a ; Li et al, 2021b ). Of course, it is not possible to absolutely polarize macrophages towards a particular subtype, as this would not only not trigger regeneration, but might make even the most basic wound healing difficult.…”
Section: Macrophages and Tissue Regenerationmentioning
confidence: 99%
“…Previous studies have mostly focused on the observation and description of the phenotype, morphology, and mechanism of macrophages that promote tissue damage by inducing an immune response ( Rayees et al, 2020 ; Zhang et al, 2020a ; Zhang et al, 2020b ; Li et al, 2021a ; Li et al, 2021b ). With the gradual development of regenerative medicine and modern molecular biology, recent studies have found that macrophages play an important role in promoting the regeneration of different tissues such as the heart, liver, kidney, muscle, and nerve.…”
Section: Introductionmentioning
confidence: 99%